Modelling performance by continents in swimming - Yustres Amores, I.; Santos del Cerro, J.; González-Mohíno, F.; Hermosilla, F.; González-Ravé, J. M. (Frontiers in Physiology, 2023)
There is a growing interest in the scientific community about the progression and consistency in the performance of talented participants who compete representing different nations in the most important international events. The prediction of future performances is now a sought-after strategy to be able to make the best return in talent investment. Numerous talent identification programs aimed at selecting and developing sports talent have been proposed over recent years. However, to our knowledge, there is a lack of research about success in swimming world championships performance considering Continents-country and how successful outcomes are influenced by these variables. Therefore, the primary goal is to analyze the effect of early specialization comparing the performance progression model of the countries gathered by continents. Participant’s data from all Junior and Senior World Championships (WCs) between 2006 and 2017 from FINA. One-way ANOVA, ANCOVA and regression model were used to explain whether the variable category, age, best z-score, experience, and continent influences the performance obtained in Absolute WC. Significant differences (p < .01) were found between the average performance obtained by the two different categories (junior: swimmers participating in junior WCs before senior WCs; senior: swimmers participating in senior WCs without previous participation in junior WCs), where swimmers from category junior showed significant better performance’s times than seniors, except in America. ANCOVA results showed that generally, the greatest differences where in the earliest ages, with best performance registered in category junior in all the continents. Also, the experience was a significant variable in the general model. Swimmers who had participated in junior category prior absolute obtained better performance’s times than those swimmers who participated directly in absolute, in the first participation in senior WC. Thus, early specialization is a key factor to obtain better results in senior WCs for all the continents, except in America.